Application of microbial fuel cell technology for vinasse treatment and bioelectricity generation - Ottoni, Cristiane Angélica [UNESP]; Simões, Marta F.; Santos, Jonas G.; Peixoto, Luciana; Martins, Cleiton R. [UNESP]; Silva, Bruno P. [UNESP]; Neto, Almir O.; Brito, António G.; Maiorano, Alfredo E. (Springer Nature, 2019)
Objective: Our study evaluated the performance of different two-chambered microbial fuel cell (MFC) prototypes, operated with variable distance between electrodes and Nafion membrane and specific inoculum concentration, applied for vinasse treatment. Results: The performance of the developed MFC resulted in a maximum current density of 1200 mA m −2 and power density of 800 mW m −2 in a period of 61 days. MFC performed a chemical oxygen demand removal at a rate ranging from 51 to 60%. Conclusions: Taking our preliminary results into consideration, we concluded that the MFC technology presents itself as highly promising for the treatment of vinasse.
Keywords: Bioelectricity; Chemical oxygen demand; Microbial fuel cell; Vinasse